Phytochemical study of Hedychium malayanum (Zingiberaceae) - Mohamed Yahya Abdo; Wan Yaacob Wan Ahmad; Laily Din; Nazlina Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2017)
A phytochemical study was conducted on the stems and leaves of Hedychium malayanum (Zingiberaceae). Three steroids namely stigmasterol (1), sitostenone (2) and stigmast-4-ene-3,6-dione (3) as well as one triterpene, lupenone (4) and one oxygenated sesquiterpene, caryophyllene oxide (5) were successfully isolated from the respective stems and leaves, utilizing several chromatographic techniques. Their structures were elucidated by spectroscopic means (IR, MS, NMR), and by comparison with the literature data.